Ұлттық сана және оның негізгі түсініктері - Nasimov, М.Ө. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
In program article President of the Republic of Kazakhstan N.A. Nazarbayev «Course towards the future: modernization of Kazakhstan’s identity» analyzed on national identity in the 21st century. In article three main aspects consciousness are defined such as: understanding what’s going on in the world, it means being open to the changes that the technological revolution brings, the ability to adopt and learn from the experience of other people and countries. In this article special attention is paid to national consciousness and its basic concepts. This work substantiates the relevance and importance of theoretical understanding of the basic concept of national consciousness. Some theoretical problems of becoming and development of national consciousness are presented. Views, some conceptual ideas domestic, foreign scientists on a problem national consciousness are considered and analyzed. The role of national consciousness in development of social, political and economic life of society is defined